DARI "BAHASA, BANGSA" HINGGA "GIGOLO" - Sudartomo Macaryus; Bambang Dwiratno (CARAKA, 2018)
The focus of this paper is to explain the potential of poetry as a source of historical information. The source of the data was taken from Antologi Puisi Indonesia: Kumpulan Pilihan Yayasan Lontar with the subtitle “Melacak Sejarah Bangsa Abas ke-20 Melalui Puisi “. The subtitle shows the use of poetry as a source of historical information. This is reasonable because poetry is the result of poet's reflection on the environment (nature, social, and culture) that he lives. Historical events are part of social phenomena which are lived by poets. The absorbed phenomenon is reflected by utilizing thoughts, feelings, desires, hopes, and all of his life experiences. In relation to history, literary works have the potential to foster empathy and affective values of the reader. In this anthology, dichotomically poetry is grouped into two periods, namely pta-RIS and Pasca-Ris. Furthermore, each of them is further classified based on years that show certain historical developments. Early period of the development of Indonesian poetry, informs admiration for the wealth and charm of the Nusantara. The work of Taufiq Ismail gathered in Tirani is closer to the historical events that occurred during the transfer of power from the Orde Lama (Old Order) to the Orde Baru (New Order). Until recent developments, the poems written in this anthology show various social events ranging from problems of corruption, hunger, education, and prostitution. Smooth and soft packaging in poetic format makes various social phenomena a symptom that causes anxiety, compassion and pity.